2018
DOI: 10.7717/peerj.5537
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and predicted functional analysis of the gut microbiota of Radix auricularia (Linnaeus) via high-throughput Illumina sequencing

Abstract: Due to its wide distribution across the world, the snail Radix auricularia plays a central role in the transferal of energy and biomass by consuming plant biomass in freshwater systems. The gut microbiota are involved in the nutrition, digestion, immunity, and development of snails, particularly for cellulolytic bacteria, which greatly contribute to the digestion of plant fiber. For the first time, this study characterized the gut bacterial communities of R. auricularia, as well as predicted functions, using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 71 publications
1
44
1
Order By: Relevance
“…The results showed that unclassified genera of Mycoplasmataceae and Chloroflexaceae, Paracoccus , Microcoleus , Pleurocapsa , etc. were the most abundant genera [14]. In contrast, our study found that Ochrobactrum , Sediminibacterium , Desulfovibrio , an unclassified genus of Aeromonadaceae, and Cloacibacterium were dominant bacteria in the gut of P. canaliculata snails.…”
Section: Discussionmentioning
confidence: 73%
“…The results showed that unclassified genera of Mycoplasmataceae and Chloroflexaceae, Paracoccus , Microcoleus , Pleurocapsa , etc. were the most abundant genera [14]. In contrast, our study found that Ochrobactrum , Sediminibacterium , Desulfovibrio , an unclassified genus of Aeromonadaceae, and Cloacibacterium were dominant bacteria in the gut of P. canaliculata snails.…”
Section: Discussionmentioning
confidence: 73%
“…The gut microbial communities of wild frogs were similar in composition between the different developmental stages in frogs in the same habitats and with similar food compositions, or under the regulation of similar physiological processes. Although previous research has confirmed that bacterial communities change during host development and growth (Hu et al, 2018), some studies have shown that bacterial communities are similar between the juvenile and adult stages of certain animal hosts (Xue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The alpha-diversity indices indicate a high diversity of the O. strigosa bacterial community, as compared with other snail species. For example, there were 7,065 total OTUs in O. strigosa, versus 1,196 OTUs in freshwater snail R. Auricularia [53]. The invasive land snail Achatina fulica only had 228 OTUs [8].…”
Section: Overall Species Microbiomementioning
confidence: 99%